FINANCING OF POLITICAL PARTIES: THEORETICAL ASPECTS OF DETERMINING THE TYPE (PRINCIPLE) OF LEGAL REGULATION - Korchak, Yaroslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: scientific substantiation of the choice of the principle that the legislator should be guided by when choosing the type of legal regulation and improving the mechanisms of state control over compliance with restrictions on political financing, including regulation of the state budget to finance the statutory activities of political parties in Ukraine. Research methods: analysis, synthesis, induction, deduction, abstraction, concretization, generalization. The constitutional requirements for the rule of law in Ukraine also apply to relations on the financing of political parties with the difference that: a) within the general permissive type of legal regulation, a political party has a state-guaranteed opportunity to act in any way and in any way; violating statutory prohibitions / restrictions; b) within the special permitting type of legal regulation, the Verkhovna Rada of Ukraine has the right to choose one of the approaches to legislative regulation of the use of state budget funds by political parties by determining an exclusive list of needs to finance their statutory activities. Results: author’s conclusions about the principles that must be considered as a criterion for choosing the type of legal regulation of relations in the field of financing of political parties. Discussion: solving the problem of determining the type of legal regulation of relations in the field of financing of political parties is associated with the correct definition of the legal nature of political parties and statutory restrictions on the sources of their funding. The term «political financing» covers relations related to the provision of material and financial support to political parties for the implementation of their statutory tasks, as well as the implementation of measures for state control over the lawful and targeted use of state funds by political parties.